On the transport properties of a nonideal plasma of underwater discharges - Starchyk, P.D.; Porytskyy, P.V. (Вопросы атомной науки и техники, 2011)
It is considered the peculiarities of the transport properties of a nonideal plasma of underwater discharges at
pressure range from 1 up to 200 bar. The transport coefficient set based on the Grad’s method is compared with the
data obtained by using of the Lorentzian plasma theory at the same plasma composition. Also, the calculation data are
considered to be in reference with transport coefficients obtained by using the Chapman-Enskog’ method. It is pointed
that the nonideality effects are needed to take into consideration under calculation of properties of underwater
discharge. Розглянуто особливості транспортних властивостей неідеальної плазми підводних розрядів в діапазоні
тисків 1...200 бар. Транспортні коефіцієнти, що були розраховані на основі методу Ґреда, порівняно із
результатами, які ґрунтувалися на лоренцевій теорії за однакового складу плазми. Також результати обчислень
порівнювалися із даними, що отримані за допомогою метода Чепмена-Енскоґа. Наголошено необхідність
взяття до уваги ефектів неідеальності плазми для розрахунку властивостей плазми підводних розрядів. Рассмотрены особенности транспортных свойств неидеальной плазмы подводных разрядов в диапазоне
давлений 1…200 бар. Транспортные коэффициенты, которые рассчитывались на основе метода Грэда,
сравниваются с результатами, полученными исходя из лоренцевой теории при одинаковом составе плазмы.
Также результаты вычислений сравниваются с данными, полученными методом Чепмена-Энскога.
Подчеркивается необходимость принятия во внимание эффектов неидеальности при расчете свойств
подводных разрядов.